Radon Concentration Measurements and Physiochemical Parameters of Sawa Lake Water-Samawa City, South of Iraq - Ahmed Augab Sharrad (Journal of Global Pharma Technology, 2016)
Radon concentration measurements were carried out for 85 water samples collected from Sawa Lake in Samawa city, Southern part of Iraq, in order to obtain the levels of radon concentration in this area and for enhancing the national radon survey. For the measurements, a continuous radon monitoring detector (RAD7) was used. The period of assessment was two months (from December, 1st 2018 to February, 1st 2019) during the winter season. Radon activity concentrations were ranged from (0.111 Bq/l) to (0.965 Bq/l), while the average value was (0.396 Bq/l), the annual effective dose (AED) of inhalation was estimated from the measured radon concentrations and is found to be ranged from (0.080784 µSvy-1) to (0.917136 µSvy-1) with a mean value of (0.325764 µSv/y). Physiochemical parameters such as pH, EC, TDS, resistivity, and turbidity were determined samples and the correlation between these parameters and radon concentrations was conducted. The results have revealed that the radon concentration and the associated annual effective dose does not pose any kind of health hazard to the population and tourists, and were found to be well within the reference levels as reported in the ICRP 2000.Keywords: Radon, Sawa Lake, Samawa City, Physiochemical Parameters, RAD7Detector.